2010
DOI: 10.1128/jvi.01519-09
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of HIV Latency in Primary CD4+Cells Is due to Epigenetic Transcriptional Silencing and P-TEFb Restriction

Abstract: The development of suitable experimental systems for studying HIV latency in primary cells that permit detailed biochemical analyses and the screening of drugs is a critical step in the effort to develop viral eradication strategies. Primary CD4 ؉ T cells were isolated from peripheral blood and amplified by antibodies to the T-cell receptor (TCR). The cells were then infected by lentiviral vectors carrying fluorescent reporters and either the wild-type Tat gene or the attenuated H13L Tat gene. After sorting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
316
8
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(343 citation statements)
references
References 57 publications
17
316
8
2
Order By: Relevance
“…As the infected cells revert to a metabolically quiescent state, productive transcription of the integrated provirus is shut down (44). Transcription elongation is a major checkpoint in the HIV-1 life cycle, and it has been demonstrated that in order for the latent reservoir to be purged or reactivated, it will likely be essential to activate P-TEFb (10,44). Therefore, it is necessary to understand the ϩ T cells generated as described in Materials and Methods were cultured in the absence or presence of the proteasome inhibitor MG132 for 2 h or 4 h. Cell lysates were probed for the expression of Cyclin T1 (A), PPM1A (B), HSP90 (C), and anti-actin (␣-Actin) antibody (loading control) in immunoblots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the infected cells revert to a metabolically quiescent state, productive transcription of the integrated provirus is shut down (44). Transcription elongation is a major checkpoint in the HIV-1 life cycle, and it has been demonstrated that in order for the latent reservoir to be purged or reactivated, it will likely be essential to activate P-TEFb (10,44). Therefore, it is necessary to understand the ϩ T cells generated as described in Materials and Methods were cultured in the absence or presence of the proteasome inhibitor MG132 for 2 h or 4 h. Cell lysates were probed for the expression of Cyclin T1 (A), PPM1A (B), HSP90 (C), and anti-actin (␣-Actin) antibody (loading control) in immunoblots.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that various factors operating at the levels of transcription and posttranscription can restrict the expression of the integrated provirus in resting CD4 ϩ T cells (5,6). Transcriptional blocks to productive HIV-1 replication include epigenetic modifications at the viral long terminal repeat (LTR) and inadequate availability of activation-dependent transcription factors such as P-TEFb, NF-B, NFAT, Sp1, AP-1, and C/EBP (7)(8)(9)(10). Posttranscriptional factors regulating viral latency include inhibition of viral mRNA export to the cytoplasm and regulation of viral gene expression by cellular microRNAs (miRNAs) (11)(12)(13).…”
mentioning
confidence: 99%
“…Ainsi, tous les inhibiteurs de P-TEFb identifiés à ce jour inhibent efficacement la réplication du virus. Un taux restreint de P-TEFb actif, associé à la mise en place d'une structure chromatinienne restrictive au niveau du promoteur LTR, semble être à l'origine de l'établissement de la latence du virus dans les cellules T CD4 + primaires [22]. Dans les cellules dans lesquelles le VIH se réplique, l'équilibre entre les formes active et inactive de P-TEFb est modifié.…”
Section: Le Système De Régulation De P-tefb Cible Du Vih-1unclassified
“…Latency happens at a very low frequency; only a small number of resting CD4 + T cells (approximately one million cells) harbor replication-competent latent provirus, which can be activated by mitogens [8] . Silencing of active infection in activated T cells and immediate silent integration in resting T cells both contribute to the establishment of latency, which has been demonstrated in vitro by several research groups [9][10][11][12] . The molecular mechanisms associated with latency are not completely understood [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…These can be categorized into the following groups, mainly based on pharmacological targets ( Figure 1): (1) histone deacetylase inhibitors (HDACi); (2) cytokines and chemokines; (3) DNA methyltransferase inhibitors (DNMTI); (4) histone methyltransferase inhibitors (HMTI); (5) protein kinase C (PKC) activators; (6) P-TEFb activators; and (7) unclassified agents, such as disulfram [9] . These compounds have been suggested as agents to reactivate HIV-1 and eradicate viral reservoirs.…”
Section: Therapeutics Used In Reactivating Latent Virusmentioning
confidence: 99%